SOLAR RADIATION AVAILABILITY FOR GROWTH OF TOMATOES DURING THE WINTER IN RIO GRANDE DO SUL - BURIOL, GALILEO ADELI (2000)
In order to indicate the most favorable regions for the cultivation of tomatoes in greenhouse, the monthly average of global solar radiation and the number of days with radiation equal and lower than 8,4 MJ.m -2 d-' was measured based on the lower criticai trophic limit of this crop and the probability of monthly ocurrence of averages equal or lower than that value, from April to September in the State of Rio Grande do Sul . Data collected from 24 meteorological stations of the Fundação Estadual de Pesquisa Agropecuária — FEPAGRO/SCT, located at different climatic regions were, utilized considering the1957 - .1997 period. In general the monthly average for the Depressão Central, Campanha, Serra do Nordeste, and Litoral regions was lower than 8,4 Mim -3 d' in June and July and for the Serra do Sudeste, Missões, Planalto, and Vale do Uruguai the average for the winter months stayed above the criticai limit.